High-intensity exercise and carbohydrate supplementation do not alter plasma visfatin - Mellick, P. F.; Feger, B. J.; Oberlin, D. J.; Davis, P. G.; Wideman, L. (Journal of Sports Science & Medicine, 2017)
The purpose of the study was to examine the effect of high-intensity exercise and carbohydrate supplementation (CHO) on plasma visfatin. On 2 separate days, 10 sprint-trained males (age = 26.4 ± 5.3 yr; Ht = 1.77 ± 0.03 m; Wt = 78.78 ± 9.10 kg; BF% = 13.96 ± 7.28%) completed 4, 3-min bouts of cycling at 50% mean anaerobic power, with 6 min of rest between bouts. On CHO day, subjects ingested 50g of CHO 30 min before exercise. On control day, subjects ingested a sugar-free drink (CON) 30 min before exercise. Blood was drawn before supplementation, 15 min before exercise, before and after each exercise bout, and 15 and 30 min post exercise. Visfatin, glucose, and insulin were determined. Truncal fat was assessed by dual energy x-ray. Visfatin was not significantly different between treatments (CHO vs CON) at any time point (p = 0.163), and was not significantly altered by exercise (p = 0.692). Insulin [25.65 vs 8.35 mU/l, CHO vs CON, respectively] and glucose [138.57 vs 98.10 mg/dl, CHO vs CON, respectively] were significantly elevated after CHO ingestion and remained elevated throughout the first half of exercise. Baseline visfatin was significantly correlated with truncal fat (r2 = 0.7782, p < 0.05). Visfatin was correlated to truncal fat in sprint-trained males, but was not altered by exercise or CHO supplementation.